Arrest of endotoxin-induced hypotension by transforming growth factor beta1. - Perrella, M A (1996)
Septic shock is a cytokine-mediated process typically caused by a severe underlying infection. Toxins generated by the infecting organism trigger a cascade of events leading to hypotension, to multiple organ system failure, and frequently to death. Beyond supportive care, no effective therapy is available for the treatment of septic shock. Nitric oxide (NO) is a potent vasodilator generated late in the sepsis pathway leading to hypotension; therefore, NO represents a potential target for therapy. We have previously demonstrated that transforming growth factor (TGF) beta1 inhibits inducible NO synthase (iNOS) mRNA and NO production in vascular smooth muscle cells after its induction by cytokines critical in the sepsis cascade. Thus, we hypothesized that TGF-beta1 may inhibit iNOS gene expression in vivo and be beneficial in the treatment of septic shock. In a conscious rat model of septic shock produced by Salmonella typhosa lipopolysaccharide (LPS), TGF-beta1 markedly reduced iNOS mRNA and protein levels in several organs. In contrast, TGF-beta1 did not decrease endothelium-derived constitutive NOS mRNA in organs of rats receiving LPS. We also performed studies in anesthetized rats to evaluate the effect of TGF-beta1 on the hemodynamic compromise of septic shock; after an initial 25% decrease in mean arterial pressure, TGF-beta1 arrested LPS-induced hypotension and decreased mortality. A decrease in iNOS mRNA and protein levels in vascular smooth muscle cells was demonstrated by in situ hybridization and NADPH diaphorase staining in rats treated with TGF-beta1. Thus these studies suggest that TGF-beta1 inhibits iNOS in vivo and that TGF-beta1 may be of future benefit in the therapy of septic shock.